2016
DOI: 10.1136/esmoopen-2016-000053
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the management of chemotherapy-induced peripheral neuropathy in Japan: Japanese Society of Medical Oncology

Abstract: BackgroundVarious drugs are administered for the management of chemotherapy-induced peripheral neuropathy (CIPN) in Japan. However, there have been no surveys undertaken to identify these drugs or their frequency of prescription. Therefore, we administered a questionnaire survey to the diplomates of the Subspecialty Board of Japanese Society of Medical Oncology (JSMO) to investigate the frequency of administration of different drugs for the management of CIPN in Japan.MethodsWe investigated the use of vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…It is to be noted that all of paclitaxel-treated gynecologic cancer patients received platinum agents, while nobody of paclitaxel-treated breast cancer patients was treated with platinum agents in the present study, thereby providing a potential bias. It is also noteworthy that the total paclitaxel dose was slightly but significantly greater in gynecologic cancer patients than in breast cancer patients (see S2 Fig) . As described in the previous report from survey of the management of CIPN in Japan [21], the present study ascertained that many of female cancer patients with PIPN were prescribed with pregabalin, mecobalamin or Goshajinkigan (see Table 3) in spite of poor evidence for their effectiveness against CIPN [17,[22][23][24], while relatively few patients with PIPN received duloxetine, the only medicine that has moderate evidence for the use to treat the established CIPN [17] (see Table 3 and Fig 2). Goshajinkigan, a polyherbal medicine that legally requires a prescription to be dispensed in Japan, contains fixed proportions of 10 crude herbal extracts, i.e.…”
Section: Plos Onementioning
confidence: 70%
See 2 more Smart Citations
“…It is to be noted that all of paclitaxel-treated gynecologic cancer patients received platinum agents, while nobody of paclitaxel-treated breast cancer patients was treated with platinum agents in the present study, thereby providing a potential bias. It is also noteworthy that the total paclitaxel dose was slightly but significantly greater in gynecologic cancer patients than in breast cancer patients (see S2 Fig) . As described in the previous report from survey of the management of CIPN in Japan [21], the present study ascertained that many of female cancer patients with PIPN were prescribed with pregabalin, mecobalamin or Goshajinkigan (see Table 3) in spite of poor evidence for their effectiveness against CIPN [17,[22][23][24], while relatively few patients with PIPN received duloxetine, the only medicine that has moderate evidence for the use to treat the established CIPN [17] (see Table 3 and Fig 2). Goshajinkigan, a polyherbal medicine that legally requires a prescription to be dispensed in Japan, contains fixed proportions of 10 crude herbal extracts, i.e.…”
Section: Plos Onementioning
confidence: 70%
“…The moderate usefulness of duloxetine for treatment of CIPN in cancer patients treated with various cytotoxic chemotherapeutics including paclitaxel has also been supported by clinical trials in Japan [19,20]. Nonetheless, apart from opioids and non-steroidal anti-inflammatory drugs (NSAIDs) that are often used to treat cancer pain, vitamin B12, pregabalin and Goshajinkigan, a Chinese polyherbal medicine, in addition to duloxetine, are commonly prescribed for treatment of CIPN in Japan [21], although there is poor evidence for their effectiveness against CIPN [17,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point underlines the expected difficulties to manage neuropathic pain in CIPN patients. Especially since recent studies in Japan ( Hirayama et al, 2016 , 2020 ), France ( Selvy et al, 2020 ; 2021a ; 2021b ) and United States ( Gewandter et al, 2020 ) have shown that oncologists do not prescribe duloxetine, or prescribe it very little, for the management of chronic pain related to CIPN. Secondly, we advise clinicians to consider particular attention to aggravating factors or factors related to the presence of severe CIPN, such as those listed above.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment strategies for CIPN are based on symptom management and include mostly neuropathic pain medication (e.g., opioids, tricyclic antidepressants, anticonvulsants, serotonin-norepinephrine reuptake inhibitors, and nonsteroidal anti-inflammatory agents) and nutritional supplements. [20][21][22][23][24][25] Experimental treatment options consist of antioxidants (e.g., alpha-lipoic acid, glutathione, and vitamin E), substances influencing ion channels (calcium/magnesium supplementation, pregabalin, and carbamazepine), and neuroprotectors (ginkgo biloba, glutamine). 20,[22][23][24]26,27 However, results are limited and no gold standard to manage CIPN has been identified to date.…”
Section: Current Treatment Strategiesmentioning
confidence: 99%